Beliefs about Pedophilia and the Attribution of Punishment for Child Sexual Abusers - Gabriela GROZA; Codruța Anamaria RÎNDAȘU (Studia Universitatis Babeş-Bolyai. Psychologia-Paedagogia)
Pedophilia is a mental illness which may or may not lead to sexual abuse against children. However, when thinking about people with pedophilic sexual interests, people often consider them abusers (even if they did not act against children and did not commit any offense). This is a pilot study aimed to explore the attitudes and perception of people with pedophilic sexual interests in Romania, based on a questionnaire that was distributed on social media (Facebook), having 1077 respondents. The questions concerned the perception of people who sexually abused children and people with pedophilia who did not abused children. The majority of participants in the study believe that people with pedophilia do not have control over their actions, even if they are perceived as ill or criminals. The results of this study have shown that chemical castration is the most preferred punishment for persons who sexually abuse children. Regarding the danger of people with pedophilia, all the respondents believed that it did not matter whether they were just suffering from an illness or if they committed and offence, they were all very dangerous. Regarding the recidivism rate, the majority of the respondents believed that the percentage is between 80-100%. Roughly half of the respondents who have children perceived 100% chances for the people with pedophilia to relapse. Further consideration and implications were discussed.